Analisis Peraturan Madrasah dan Kedisiplinan Santri di MA NWDI Ketangga : Penelitian - Maesa Saputra; Hasrul Hadi; Khairil Tamimi; Kailani Guswiati Arni; Vina Cahya Agustina (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the role of madrasa regulations in shaping student discipline at Madrasah Aliyah (MA) Nahdlatul Wathan Diniyah Islamiyah (NWDI) Ketangga, Selong, East Lombok. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and document analysis involving 50 students from grades X–XII, 2 teachers, and 3 school administrators. The findings indicate that the implementation of strict madrasa regulations—such as rules on prayer schedules, attendance, and the prohibition of gadget use—effectively increased student discipline by up to 85% according to survey results. However, challenges remain, including external environmental influences and inconsistent enforcement of sanctions. The study also emphasizes that student discipline is a crucial factor in creating an effective learning environment and fostering Islamic character development. Recommendations include strengthening the socialization of school regulations and integrating Islamic values into disciplinary guidance, enabling the madrasa to create a conducive learning atmosphere and nurture students who are disciplined, responsible, and morally upright.